Association between serum albumin-to-globulin ratio and subtypes of cerebral atherosclerotic stenosis in acute ischemic stroke - Fu, Yu-xin; Cao, Jie; Yin, Xiang; Lang, Yue; Su, Teng-fei; Cui, Li (Frontiers in Neurology, 2025)
BackgroundThe albumin-to-globulin ratio (AGR) is a biomarker reflecting both nutritional status and inflammation, which has recently been implicated in the development of ischemic stroke. However, its potential association with the occurrence of cerebrovascular stenosis remains unclear. This study aimed to investigate the relationship between AGR and the incidence of cerebral atherosclerotic stenosis.MethodsData from 766 adult patients with acute ischemic stroke (AIS) were included in this cross-sectional analysis. Binary logistic regression was used to evaluate the independent association between AGR and the risk of various cerebrovascular stenosis, including anterior circulation stenosis, posterior circulation stenosis, intracranial and extracranial stenosis. To explore the potential non-linear relationship between AGR and these outcomes, restricted cubic spline models were employed to further clarify these associations. Stratified analyses by body mass index (BMI), age, and sex were additionally conducted to explore the correlation between AGR and cerebral atherosclerotic stenosis under different conditions.ResultsPatients with cerebral atherosclerotic stenosis had lower AGR levels than those without corresponding vascular stenosis. After adjusting for multiple covariates, AGR levels were negatively associated with the presence of stenosis in the posterior circulations (OR = 0.59, 95%CI = 0.38 ~ 0.90, p = 0.015) and intracranial stenosis (Q4: OR = 0.55, 95% CI = 0.34 ~ 0.89, p = 0.015). This association was essentially unaffected by BMI, age, or sex. Furthermore, a negative linear relationship was observed between AGR levels and the occurrence of posterior circulation stenosis (p for overall = 0.001, p for non-linear = 0.228) and intracranial vascular stenosis (p for overall <0.001, p for non-linear = 0.440).ConclusionHigher AGR is associated with a reduced risk of multiple cerebral atherosclerotic stenosis. AGR levels are significantly associated with the presence of specific stenosis subtypes and could be hypothesized as a marker for risk stratification; this utility requires validation in prospective cohorts.